Prevalência da enteropatia proliferativa suína causada por Lawsonia intracellularis em suínos de abate no estado de Mato Grosso - Alberton, Evandro Luiz (2008)
This study aimed to determine the prevalence of porcine proliferative enteropathy in pigs slaughtered in Mato Grosso, State Brazil, through the observation of pigs microscopic intestinal lesions and morphological structures compatible with the bacteria Lawsonia intracellularis in enterocytes. The search was conducted between the months of August 2006 to July 2007, and collected 739 samples of pig ileum of 11 municipalities, on 03 Slaughterhouse under Federal and State inspection, in Mato Grosso. Showed up that 16.78% of the samples examined have lesions suggestive of proliferative enteropathy associated with L. intracellularis. Of the samples with injuries, 40.32% appear, for silver staining, like structures of the Lawsonia intracellularis within the enterocytes.